Love is blurb: Reality TVs as local tourism marketing intermediaries - Cempaka, Putri Surya (Priviet Social Sciences Journal, 2025)
Reality TV programs attract viewers from various backgrounds and age groups. Several previous studies have stated that reality TV shows can change viewers’ lifestyles. In addition, reality TV shows can provide a platform for the existence and branding of public figures. Reality TV programs can be subjectively evaluated and can have both positive and negative effects. However, to objectively assess the existence of reality TV programs, it is necessary to examine whether reality TV shows can be beneficial for the audience or the economic condition of a country. The proliferation of reality TV programs on Netflix's Video on Demand services, such as Love is Blind, The Ultimatum, and Single’s Inferno, indicates that success is generated from the production of these programs. One hypothesis is that the format of reality TV programs emphasizes certain tourist destinations. Thus, reality TV programs can be utilized as mediums or intermediaries for promoting and marketing tourism in specific regions or countries.